IL-10-Producing B Cells Regulate T Helper Cell Immune Responses during 1,3-β-Glucan-Induced Lung Inflammation - Liu, Fangwei; Lu, Xiaowei; Dai, Wujing; Lu, Yiping; Li, Chao; Du, Sitong; Chen, Ying; Weng, Dong; Chen, Jie (Frontiers in Immunology, 2017)
With the rapid development of industry and farm, fungi contamination widely exist in occupational environment. Inhalation of fungi contaminated organic dust results in hypersensitivity pneumonitis. 1, 3-β-glucan is a major cell wall component of fungus and is considered as a biomarker of fungi exposure. Current studies showed that 1, 3-β-glucan exposure induced lung inflammation, which involved uncontrolled T-helper (Th) cell immune responses, such as Th1, Th2, Th17and regulatory T cell (Treg). A recently identified IL-10-producing B cells (B10) was reported in regulating immune homeostasis. However, its regulatory role in hypersensitivity pneumonitis is still subject to debate. In our study, we comprehensively investigated the role of B10 and the relationship between B10 and Treg in 1, 3-β-glucan-induced lung inflammation. Mice with insufficient B10 exhibited more inflammatory cells accumulation and severer pathological inflammatory changes. Insufficient B10 led to increasing Th1, Th2 and Th17 responses and restricted Treg function. Depletion of Treg before the onset of inflammation could suppress B10. Whereas, Treg depletion only at the late stage of inflammation failed to affect B10. Our study demonstrated that insufficient B10 aggravated the lung inflammation mediated by dynamic shifts in Th immune responses after 1, 3-β-glucan exposure. The regulatory function of B10 on Th immune responses might be associated with Treg and IL-10. Treg only could interact with B10 at an early stage.